Uniparental disomy: expanding the clinical and molecular phenotypes of whole chromosomes - Chen, Qi; Chen, Yunpeng; Shi, Lin; Tao, Ying; Li, Xiaoguang; Zhu, Xiaolan; Yang, Yan; Xu, Wenlin (Frontiers in Genetics, 2023)
Uniparental disomy (UPD) refers to as both homologous chromosomes inherited from only one parent without identical copies from the other parent. Studies on clinical phenotypes in UPDs are usually focused on the documented UPD 6, 7, 11, 14, 15, and 20, which directly lead to imprinting disorders. This study describes clinical phenotypes and genetic findings of three patients with UPD 2, 9, and 14, respectively. Chromosomal microarray (CMA), UPDtool, methylation-specific multiplex ligationdependent probe amplification (MS-MLPA) and whole-exome sequencing (WES) analysis were performed to characterize the genetic etiology. The CMA revealed a homozygous region involving the whole chromosome 2 and 9, a partial region of homozygosity in chromosome 14. UPD-tool revealed a paternal origin of the UPD2. MS-MLPA showed hypomethylation of imprinting gene MEG3 from maternal origin in the UPD14 case. In addition, UPD14 case displayed complex symptoms including growth failure, hypotonia and acute respiratory distress syndrome (ARDS), accompanied by several gene mutations with heterozygous genotype by WES analysis. Furthermore, we reviewed the documented UPDs and summarized the clinical characteristics and prognosis. This study highlighted the importance to confirm the diagnosis and origin of UPD using genetic testing. Therefore, it is suggested that expanding of the detailed phenotypes and genotypes provide effective guidance for molecule testing and genetic counseling, and promote further biological investigation to the underlying mechanisms of imprinted disorders and accompanied copy number variations.